Regulatory T Cells in GVHD Therapy - Guo, Wen-wen; Su, Xiu-hua; Wang, Ming-yang; Han, Ming-zhe; Feng, Xiao-ming; Jiang, Er-lie (Frontiers in Immunology, 2021)
Graft versus host disease (GVHD) is the leading cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT) as one of the common complications. Pharmacological immunosuppression used in GVHD prophylaxis and treatment lacks specificity and can increase the chances of infection and relapse. Regulatory T lymphocytes (Tregs) play a vital role of restraining excessive immune response and inducing peripheral immune tolerance. Particularly, Tregs has the capacity to prevent and treat GVHD without increasing the risk of relapse and infection in clinical trials. Using the properties of immunosuppression, adoptive transfer of Tregs to control GVHD may represent a promising therapy. In order to achieve the optimal use of Tregs in controlling GVHD, making a thorough understanding of Tregs is necessary. In the review, we will describe characteristics of Tregs biology and how to maintain the stability of Foxp3 expression. We will also illustrate the mechanisms of Tregs to modulate GVHD and approaches to increase Tregs numbers effectively. In the end, we will discuss the development trend of Tregs in clinical therapy.